2000
DOI: 10.1055/s-2000-7496
|View full text |Cite
|
Sign up to set email alerts
|

MR Patterns of Hypoxic-Ischemic Brain Damage After Prenatal, Perinatal or Postnatal Asphyxia*

Abstract: The relationship between MR patterns of brain damage and type or timing of perinatal hypoxia-ischemia was studied. MR images of 104 children with evidence of bilateral posthypoxic-ischemic brain damage and neonatal records were reviewed. Three different MR patterns were found. Periventricular leukomalacia occurred in 73 children, in 82% after a history of subacute or chronic hypoxia-ischemia, in 71% after preterm birth. Predominant lesions of basal ganglia and thalamus occurred in 21 children, in 95% preceded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(130 citation statements)
references
References 33 publications
(56 reference statements)
4
115
0
6
Order By: Relevance
“…It is also observed by Sie U et al, 6 where PV leukomalacia in 82% after subacute or chronic hypoxia and in preterm babies.…”
Section: Severity Of Involvementsupporting
confidence: 61%
See 1 more Smart Citation
“…It is also observed by Sie U et al, 6 where PV leukomalacia in 82% after subacute or chronic hypoxia and in preterm babies.…”
Section: Severity Of Involvementsupporting
confidence: 61%
“…In the study by Sie U et al, 6 also found that multicystic encephalopathy in 70% preceded by mild hypoxic ischaemia. It is observed that those babies having profound asphyxia (Stage III), 50% showed involvement of thalamus, 25% showed involvement of basal ganglia and 25% showed involvement of brainstem.…”
Section: Severity Of Involvementmentioning
confidence: 99%
“…On early (Յ4 days) PWI-MRI, marked hyperperfusion (increased rCBF and rCBV) was seen in areas of HI brain damage, allowing for classification of the children into the different known patterns of HI injury (1,13,14): 1 infant demonstrated a normal pattern (patient 1); 1 a watershed pattern (patient 2); 1 a basal ganglia pattern (patient 3); and 2 a total cortical pattern (patients 4 and 5). These patterns were confirmed on early diffusionweighted imaging (DWI), on late (9 to 11 days) conventional MRI (T2-weighted images) or on postmortem examination in all infants.…”
Section: Resultsmentioning
confidence: 99%
“…We did not include infants with WM damage only as it is less likely that this pattern results from acute perinatal hypoxia-ischemia alone. 1,28,30 We know that in children with a history of HIE and WM damage in the absence of BGT injury the rate of CP and death is very low; in a study of 46 such infants none died, only 6 developed CP, and all but 2 were walking by 2 years. 31 We also excluded infants treated with hypothermia as at the start of this study it was not known whether this therapy might alter the relationship between imaging and outcome.…”
Section: Discussionmentioning
confidence: 99%